Child Marriage Law and Women Protection: Human Rights Lessons from India, China, and Indonesia - Salim Bashir Magashi; Uche Nnawulezi; Septhian Eka Adiyatma; Oluwatobiloba Ifedolapo Ajayi (Universitas Negeri Semarang, 2026)
Despite universal recognition of child marriage as a fundamental violation of human rights, ratified by global instruments like the Convention on the Rights of the Child (CRC) and CEDAW, the practice persist significantly in India, China and Indonesia, challenging the efficacy of existing national legal frameworks. The paper critically analyze and compare the legal frameworks, enforcement mechanisms, and normative challenges surrounding child marriage prevention in India, China, and Indonesia, assessing their compliance with international human rights standards and identifying the effectiveness of legal interventions in mitigating socio-cultural drivers of early marriage. The paper employs a normative juridical approach, and through a comparative analysis of primary legal sources like statutes, constitutions, and secondary sources like court decisions, international conventions, and reports to analyze the differences and similarities in legal protection. It utilize a comparative analytical method to identify strengths and weaknesses in each country's approach. The consequences resulting from this are: to what extent does legal exemptions, personal laws, and rural customary practices in India, China, and Indonesia create inconsistencies between national legislation and international human rights obligations? What are the primary enforcement gaps and challenges in the implementation of anti-child marriage laws in each jurisdictions, specifically regarding legal age verification and prosecution of offenders? To what extent does the current legal frameworks in all three countries prioritize the best interests of the child over parental consent or religious and cultural norms? How does the different approaches to child marriage criminalization in India, administrative control in China, and modified consent in Indonesia affect the prevalence rates and legal rights of children in rural areas against urban settings? These questions form the basis of this paper. The paper reveals that despite the 2019 reform in Indonesia, significant legal gaps exist, as religious courts often grant exemptions for under-age marriages, particularly due to out-of-wedlock pregnancy. In India, a major issue is the conflict between the secular PCMA and personal laws, while China generally maintain higher minimum age standards than its neighbors, reducing the absolute number of child brides, though it still has significant numbers concentrated in rural, lower-income regions. It concludes that while India, China, and Indonesia have significantly strengthened their national legal frameworks to align with international human rights standards, the effective prevention of child marriage is currently hindered by a widening enforcement -norm gap.